METHOD FOR DRYING MAIZE POLLEN - Indri Fariroh; Riza Yuli Rusdiana (Jurnal Penelitian Pertanian Terapan, 2020)
Pollen managements consisted of suitable harvest timing, pollen drying to a certain misturecontent, pollen viability testing, and pollen storage. Maize pollen was sensitive todesiccation. This experiment was aimed to determine preservation technique in reducingpollen water content while maintaining its viability. Maize variety which used in thisresearch was BIMA 3 as male line hybrid maize. Pollen viability testing used potassiumiodide (KI) 1%. This experiment used randomized block design with 3 factors and 2 replicates, i.e. boron (H3BO3) fertilizers (0 and 3 kg ha-1), drying techniques (MgCl2, silicagel, zeolite and preservation in air-cond room (18Â±1 Â°C; RH 43%), and drying periods (0,2, 4, 6 and 8 hours). The observation response of this experiment were viability and pollen weight changing. The result showed that there is no interaction between three factors to observation response, while drying technique and drying period combinations showed interactions to observation response. Pollen maize drying used silica gel for 4 hours was able to decline much pollen weight and maintain pollen viability better than other techniques.